Impact of radiation therapy dose, fractionation, and immunotherapeutic partner in a mouse model of hormone receptor-positive mammary carcinogenesis - Buqué, Aitziber; Bloy, Norma; Petroni, Giulia; Jiménez-Cortegana, Carlos; Sato, Ai; Iribarren, Cristina; Yamazaki, Takahiro; Galassi, Claudia; Hensler, Michal; Bhinder, Bhavneet; Guarracino, Andrea; Rippon, Brady; et al. (Journal of the National Cancer Institute, 2025)
BACKGROUND: Hormone receptor-positive (HR+) breast cancer responds poorly to immune checkpoint inhibitors (ICIs). In some settings, radiation therapy (RT) has been shown to mediate immunostimulatory effects and promote ICI sensitivity. METHODS: We investigated whether hypofractionated RT may be successfully combined with ICIs in a mouse model of multifocal, metachronous HR+ mammary carcinogenesis. We hypothesized that focal RT targeting the first detectable (primary) tumor combined with ICIs may generate effective immunity, delaying the development of new lesions. RESULTS: Focal RT in various doses and fractionations limited primary tumor growth, with an optimum for a 20-Gy × 2 regimen (ablative in approximately 90% of mice). The degree of primary disease control, however, did not necessarily correlate with overall survival extension because of changes in the development of new neoplastic lesions contributing to global tumor burden. Adding a PD-1 blocker to focal RT delivered in a 10-Gy × 3, 20-Gy × 2, or 8-Gy × 6 regimen failed to alter overall survival extension enabled by RT alone. Similar results were obtained with a CTLA4 blocker, an IL-1β inhibitor, and a PD-1 blocker plus recombinant FLT3LG when combined with the 10-Gy × 3 regimen. CONCLUSIONS: In this model of HR+ mammary carcinogenesis, RT to the primary tumor ameliorates overall survival (to an extent based on dose and fractionation). Increasing local control through RT alone or RT plus immunotherapy beyond a hitherto undefined threshold, however, does not necessarily inhibit the development of subsequent nonirradiated neoplasms and hence does not necessarily provide extra overall survival benefits.
Keywords: antigeny CD279; nádory prsu; Programmed Cell Death 1 Receptor; Radiation Dose Hypofractionation; Animals; Combined Modality Therapy; Dose Fractionation, Radiation; Mice; receptory pro estrogeny; Receptors, Progesterone; Female; hypofrakcionace při ozařování; Mammary Neoplasms, Experimental; modely nemocí na zvířatech; frakcionace dávky záření; ženské pohlaví; imunoterapie; kombinovaná terapie; receptory progesteronu; zvířata; experimentální nádory mléčných žláz; Receptors, Estrogen; Immune Checkpoint Inhibitors; inhibitory kontrolních bodů; Immunotherapy; Disease Models, Animal; Breast Neoplasms; myši